2011
DOI: 10.1093/humrep/der036
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cell gene expression predicts better cleavage-stage embryo or blastocyst development and pregnancy for ICSI patients

Abstract: Multivariable models based on CC gene expression can be used to predict embryo development and pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 34 publications
(41 reference statements)
9
115
2
1
Order By: Relevance
“…The 4-fold down-regulation of GREM1 gene expression seen may indicate impaired oocyte function and cumulus GC expansion, associated with poor reproductive outcome. It has been previously shown that increased GREM1 expression in cumulus GC's is a positive predictor of oocyte maturity, fertilization, embryo development and pregnancy rate in women undergoing IVF [6][7][8][9][10][11]. Our data suggests a corollary to these findings: that a decrease in GREM1 expression in cumulus GC's is specific to women with diminished reproductive potential.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The 4-fold down-regulation of GREM1 gene expression seen may indicate impaired oocyte function and cumulus GC expansion, associated with poor reproductive outcome. It has been previously shown that increased GREM1 expression in cumulus GC's is a positive predictor of oocyte maturity, fertilization, embryo development and pregnancy rate in women undergoing IVF [6][7][8][9][10][11]. Our data suggests a corollary to these findings: that a decrease in GREM1 expression in cumulus GC's is specific to women with diminished reproductive potential.…”
Section: Discussionsupporting
confidence: 65%
“…Growth and differentiation factor 9 (GDF9) and its homologues bone morphogenic protein 15 (BMP15, also known as GDF9ß) and BMP6 are currently regarded as the best candidate molecules responsible for oocyte regulation of cumulus GC expansion during ovulation, which is imperative for normal oocyte development in vivo [5]. GDF9 induces cumulus GC gene expression of gremlin 1 (GREM1) [5], a highly-conserved member of the differential screening-selected gene aberrative in neuroblastoma (DAN) family of secreted factors involved in regulating the balance of GDF9 and BMP15 correlated with embryonic development [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The granulosa cells of the ovarian follicle support and nurture the oocyte and secrete estrogens which establish a functional bidirectional crosstalk with the oocyte through gap junctions and paracrine factors, and GCs are necessary for normal reproductive function (Langhout et al 1991;Petro et al 2012). Several studies have been published, demonstrating that the gene expression of GCs may differ in relation to the potential development of the embryo (McKenzie et al 2004;Wathlet et al 2011). Heat stress induced the alternation of progesterone production in cumulus cells which are surrounding the bovine oocyte during Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective study, they selected an 8 gene panel, HAS2, follicle=stimulating hormone receptor (FSHR), solute carrier family 2 member 4 (SLC2A4), activated leukocyte cell adhesion molecule (ALCAM), secreted frizzled-related protein 2 (SFRP2), VCAN, NRP1 and PGR based on prior published studies (McKenzie et al 2004, Gebhardt et al 2011, Wathlet et al 2011, Fragouli et al 2012, Iager et al 2013 to predict the mature oocytes that would lead to live birth. Based on their qRT-PCR results, it was determined that HAS2, FSHR, VCAN and PGR would be the best genes to rank the oocytes.…”
Section: Predictive Modelsmentioning
confidence: 99%